Unlocking the Secrets of Arabic Learning: Implementing the Al-Syamiyyah Al-Syafahiyah Method as an Effective Alternative in Schools and Islamic Boarding Schools - Mohammad Jailani; Zaki Abouelnasr Elbaghdadi (Lahjatuna: Jurnal Pendidikan Bahasa Arab, 2024)
This research aims to analyze the contribution of the Al-Syamiyyah Al-Syafahiyyah method as a suitable foundational strategy in basic Arabic language learning. The study is motivated by the limited understanding within the education community regarding Arabic language teaching methods. The qualitative approach with descriptive analysis is used, analyzing various selected literature to answer and support the findings. Based on the research results, it can be concluded that the Al-Syamiyyah Al-Syafahiyyah method is a strategic approach that should be implemented in basic Arabic language learning. However, it is essential to consider both the strengths and weaknesses of this method, as not all aspects may be effectively implemented. This research sheds light on the significance of the Al-Syamiyyah Al-Syafahiyyah method as a valuable tool in Arabic language education and emphasizes the need for further exploration and refinement of language teaching approaches. By understanding and implementing this method effectively, educators can enhance the learning experience and proficiency of students in basic Arabic language skills.